On economic evaluation of directional forecasts - Oliver J. Blaskowitz; Helmut Herwartz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
It is commonly accepted that information is helpful if it can be exploited to improve a decision making process. In economics, decisions are often based on forecasts of up- or downward movements of the variable of interest. We point out that directional forecasts can provide a useful framework to assess the economic forecast value when loss functions (or success measures) are properly formulated to account for realized signs and realized magnitudes of directional movements. We discuss a general approach to evaluate (directional) forecasts which is simple to implement, robust to outlying or unreasonable forecasts and which provides an economically interpretable loss/success functional framework. As such, the measure of directional forecast value is a readily available alternative to the commonly used squared error loss criterion.
Keywords: C52; E17; E27; E37; E47; F17; F37; F47; G17; 330; Directional forecasts; directional forecast value; forecast evaluation; economic forecast value; mean squared forecast error; mean absolute forecast error; Prognoseverfahren; Bewertung; Statistischer Fehler; Theorie; Zinsswap; Prognose; Schätzung; EU-Staaten